The relationship between nurse behavior, waiting time, and preoperative education with preoperative patient satisfaction central surgical installation - Saimi, Saimi; Menap, Menap; AS, Iwan Kusmayadi (Science Midwifery, 2024)
In context service health , satisfaction patient be one _ indicator main in evaluate quality services provided by the house Sick . Installation service _ surgery central own role crucial in the treatment process patient before operation . Factors _ like behavior nurse , time wait , and preoperative education has identified as a number of possible factors _ influence satisfaction patients in the preoperative phase . Study This aim For know connection behavior nurse , time wait , and preoperative education with satisfaction preoperative patients in the installation surgery central . Research methods This use approach quantitative . The research location is at Patut Regional Hospital Obedient Patju , West Lombok. Respondent in research This totaling 97 people. The data collection method uses questionnaire . Research result show There is connection between behavior nurse with satisfaction patient , p This showed from r value is 0.417. Variable time wait also show There is connection with satisfaction patient , p This showed from r value is 0.624. In aspect Preoperative education also shows _ There is connection between time Wait with satisfaction patient , p This showed from r value is 0.282. Percentage satisfaction patients who are influenced by behavior nurse , time wait , and pre- operative education at the installation Central Surgery viz amounting to 51.4%, the rest 48.6 % is influenced by other variables that are not researched .